2016
DOI: 10.1016/j.brainresbull.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Toward more predictive genetic mouse models of Alzheimer's disease

Abstract: Genetic mouse models for Alzheimer’s disease (AD) have been widely used to understand aspects of the biology of the disease, but have had limited success in translating these findings to the clinic. In this review, we discuss the benefits and limitations of existing genetic models and recent advances in technologies (including high through put sequencing and genome editing) that promise more predictive models. We summarize widely used biomarkers and behavioral tests for mouse models of AD and highlight best pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 80 publications
3
105
0
1
Order By: Relevance
“…Lack of Congo red staining suggested that degree of amyloid accumulation is not as high in this Sgo1 −/+ model as existing EOAD mouse models that typically express a few‐to‐several‐fold amount of total amyloids compared with controls and show Congo red staining (Kitazawa et al., 2012; Onos et al., 2016; Sasaguri et al., 2016). The result was in agreement with immunoblots in Figure 1 indicating only mild increase in total amyloids (amyloid‐β and APP combined) in Sgo1 −/+ compared with age‐matched wild type and BubR1 −/+ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of Congo red staining suggested that degree of amyloid accumulation is not as high in this Sgo1 −/+ model as existing EOAD mouse models that typically express a few‐to‐several‐fold amount of total amyloids compared with controls and show Congo red staining (Kitazawa et al., 2012; Onos et al., 2016; Sasaguri et al., 2016). The result was in agreement with immunoblots in Figure 1 indicating only mild increase in total amyloids (amyloid‐β and APP combined) in Sgo1 −/+ compared with age‐matched wild type and BubR1 −/+ .…”
Section: Resultsmentioning
confidence: 99%
“…Major pathological features of the human AD brain include plaques of amyloid‐β made of cleaved APP, tangles of Tau proteins, and congophilic cerebral amyloid angiopathy (Kitazawa, Medeiros, & Laferl, 2012; Onos, Sukoff Rizzo, Howell, & Sasner, 2016; Sasaguri et al., 2016; Scheltens et al., 2016). With insufficient knowledge on the cause, modeling LOAD in rodents has been an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APB Tg .Mx −/+ mice. Several mouse models of AD have successfully shown extensive amyloid plaque deposition and neuroinflammation, but, in the absence of additional genetic manipulations, not many show significant neuronal loss and associated cognitive decline (Onos et al, 2015, Webster et al, 2014, Wirths and Bayer, 2010). The lack of substantial neuronal cell loss significantly limits the identification and testing of therapeutic targets for AD (Onos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research using AD mouse models have failed to translate into successful treatments for a variety of reasons, many of which have been discussed previously (Onos et al, 2016). Our results demonstrate that genetic variation profoundly affects the expressivity of the 5XFAD transgene on both cognitive and pathological traits.…”
Section: Importance Of Genetic Background In Choosing a Mouse Modelmentioning
confidence: 99%